DEVELOPMENT OF PROFESSIONAL-PEDAGOGICAL MOTIVATION OF FUTURE TEACHERS IN THE CONDITIONS OF THE INTEGRATED EDUCATIONAL AND PROFESSIONAL SPACE - Chekina, Alena; Vilchynskaya, Liudmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article is devoted to consideration of a problem of modernization of vocational training of future teachers by strengthening of its practical orientation. One of solutions of this problem is designing of the new educational space based on close interaction and integration of resources of university and organizations-customers of specialists. In article the author's model of the integrated educational-professional space of training of teachers is characterized. This model including a number of the interconnected components: target, structural, resource, substantial, procedural-activity and productive. The professional-pedagogical motivation at future teachers was studied by means of "Self-assessment of Professional-Pedagogical Motivation" by N. P. Fetiskin. This tool allows to define at what step of a motivational ladder there is a student: from indifference to future profession to the professional need to seize bases of pedagogical skill.